Impact of HOT Instruction on Knowledge and Comprehension in Chemistry and Biology for Middle School Students - Ainur Sadykova; Marzhan Iskakova; Gulnara Ismailova; Zamzagul Orazgaliyeva; Elmira Kozhakhmetova; Zhanar Nurtazina (Qubahan Academic Journal)
Higher-order thinking (HOT) have proliferated in education. While traditional didactic methods may fail to engage students effectively, research suggests the potential pros of HOT-grounded learning in terms of educational outcomes. However, there is a dearth of studies investigating the impact of such approaches on biology and chemistry education at the middle school level. Hence, this study aimed to evaluate the effectiveness of an after-school program designed to foster biological/chemical literacy and metacognitive self-regulation through meta-learning activities. A total of 132 eighth-graders took part in structured educator-led activities over a 10-week period. Sessions centered upon multi-level understanding, connecting scientific concepts, and utilizing metacognitive prompts. Controls received traditional didactic instruction aligned with the standard curriculum. Results indicated significant improvements in biology comprehension alongside chemistry knowledge and comprehension among students who completed the experimental module as compared to untreated counterparts. Per chemistry, learners reporting higher pre-existing self-regulation tended to reach better knowledge acquisition at post-test, with interference control acting as a moderator. Baseline self-regulation predicted post-intervention biology understanding as well, and the effect was moderated by interference control. These findings advocate for the integration of HOT-based training into middle school curricula to bolster attainment across science disciplines.